2016
DOI: 10.1371/journal.pone.0157063
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin Response to Iron Therapy in Patients with Non-Dialysis Dependent CKD: An Analysis of the FIND-CKD Trial

Abstract: Hepcidin is the key regulator of iron homeostasis but data are limited regarding its temporal response to iron therapy, and response to intravenous versus oral iron. In the 56-week, open-label, multicenter, prospective, randomized FIND-CKD study, 626 anemic patients with non-dialysis dependent chronic kidney disease (ND-CKD) and iron deficiency not receiving an erythropoiesis stimulating agent were randomized (1:1:2) to intravenous ferric carboxymaltose (FCM), targeting higher (400–600μg/L) or lower (100–200μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 36 publications
3
24
1
Order By: Relevance
“…Supporting the physiologic and functional significance of the reduction of hepcidin, iron stores in the setting of anemia correction (i.e., changes from baseline in ferritin and TSAT) were stable in patients receiving oral iron but declined among those not receiving any iron supplementation. Consistent with the findings of other cohort studies supporting the effect of IV iron in increasing hepcidin production, the group receiving IV iron in this study had no reduction in hepcidin . The lesser hepcidin reduction in the IV iron cohort at end of treatment may be attributable to competing feedback loops by the higher levels of circulating iron in this group, suggesting that IV iron may alter normal iron regulation and that HIF‐PHIs may play a role in minimizing iatrogenic iron overload due to IV iron.…”
Section: Roxadustat Reduced Hepcidin Levels In Phase 2 Studiessupporting
confidence: 89%
“…Supporting the physiologic and functional significance of the reduction of hepcidin, iron stores in the setting of anemia correction (i.e., changes from baseline in ferritin and TSAT) were stable in patients receiving oral iron but declined among those not receiving any iron supplementation. Consistent with the findings of other cohort studies supporting the effect of IV iron in increasing hepcidin production, the group receiving IV iron in this study had no reduction in hepcidin . The lesser hepcidin reduction in the IV iron cohort at end of treatment may be attributable to competing feedback loops by the higher levels of circulating iron in this group, suggesting that IV iron may alter normal iron regulation and that HIF‐PHIs may play a role in minimizing iatrogenic iron overload due to IV iron.…”
Section: Roxadustat Reduced Hepcidin Levels In Phase 2 Studiessupporting
confidence: 89%
“…In a study of 56 dialysis‐dependent CDK patients, Tessitore et al showed that serum hepcidin concentration was not an important predictor of a response to intravenous iron treatment in patients receiving ESA. A similar conclusion was reached by the FIND‐CKD investigators . Further studies are ongoing to determine whether and how hepcidin measurement can be used to quantify iron status in patients with CKD anemia.…”
Section: Methods Of Iron Quantificationsupporting
confidence: 68%
“…A similar conclusion was reached by the FIND-CKD investigators. 69 Further studies are ongoing to determine whether and how hepcidin measurement can be used to quantify iron status in patients with CKD anemia. An assessment of biological hepcidin variability over 2-to 6-week period suggests that short-term measurement of hepcidin might not be useful for guiding clinical decisions regarding iron status in CKD patients.…”
Section: Hepcidinmentioning
confidence: 99%
“…It is the central regulator of systemic iron homeostasis, and restricts the release of recycled iron from macrophages and iron stored in hepatocytes into the plasma, resulting in inadequate iron supply for erythropoiesis . In CKD patients, hepcidin levels have been found to be highly elevated, presumably due to inflammation‐induced upregulation, reduced renal clearance, and high iron treatment …”
Section: Introductionmentioning
confidence: 99%
“…Whether hepcidin could be used as a biomarker for hematopoietic response remains unknown. In the FIND‐CKD cohort, Gaillard et al showed in 69 patients that hepcidin was not a good prognosis factor for iron response but may be for hematopoietic response to a lesser extent . In contrast, it has been shown in anemic patients with a chronic rheumatologic disease that baseline hepcidin was a good predictor of hemoglobin response on oral iron therapy …”
Section: Introductionmentioning
confidence: 99%